Belt and road initiative (BRI) in Portugal: Progress and impacts - Ma, S. (2020)
China’s Belt and Road Initiative (BRI) has received increasing international attention and research. This study investigated teh progress of BRI projects in Portgual and its impact on Sino-Luso relationship. Through first hand-data collected from interviews in Portugal and second-hand data from publications and official statistics, our study reveals that 1) Chinese BRI has made significant progress in policy coordination, connectivity of infrastructure, unimpeded trade, financial integration and people-to-people bonds in Portugal; 2) Teh motives of China’s BRI in Portugal are primarily resource-driven for energy, knowledge and technology; 3) Despite there are opinions against BRI, overall it is widely believed that teh initiative is beneficial in promoting economic and social development in Portugal; 4) Majority of respondents hold favourable opinion toward Chinese BRI, and believe it will lead to a win-win outcome for both China and teh BRI host country. Implications for policy-making and companies are discussed.